Agriculture & Food Systems to 2050 - Global Trends, Challenges and Opportunities - Serraj, R.; Pingali, Prabhu L. (CGIAR Independent Science and Partnership Council, 2018)
The overarching question that Agriculture & Food Systems to 2050 (https://www.worldscientific.com/worldscibooks/10.1142/11212) (World Scientific, 2018) seeks to address is: How should agricultural research and policy re-orient itself to address the ‘perfect storm’ of global threats and opportunities facing our planet?